Intercultural Communicative Competence for Global Citizenship Identifying cyberpragmatic rules of engagement in telecollaboration - Orsini-Jones, Marina (Palgrave Macmillan UK, 2018)
This work builds on the assumption that language learning and teaching needs to be made more relevant to the 'glocalised' digital world we live in. Its authors argue that staff in Higher Education (HE) must prepare students for effective online interaction and explores the digital, linguistic and critical intercultural components of 'global citizenship'. The book pivots around an innovative research study; linguistic politeness frameworks are revisited to analyse the written online exchanges on an Online International Learning (OIL) - or intercultural telecollaborative - project between the UK and France.Through the use of cyberpragmatics, and inspired by Meyer and Land's 'threshold concept pedagogy', the authors examine the challenges and solutions identified by an 'expert student' in managing rules of engagement and intercultural awareness when interacting online. This book will appeal to students and scholars of applied linguistics, education, sociolinguistics and intercultural communication, and provide a valuable resource for teacher trainers, language teachers and educators across the world.